Aalto-1 Earth Observation nanosatellite mission status and in orbit experiments - Jaan Praks; Antti Kestilä; Tuomas Tikka; Antti Näsilä; Bagus Riwanto; Nemanja Jovanovic; Petri Niemelä; Nuno Silva; Rami Vainio; Pekka Janhunen (My University, 2022)
In this paper we will describe a Finnish Aalto-1 CubeSat satellite and describe the first in orbit results of the Earth Observation mission. The Aalto-1 is built by a consortium of universities and institutes and also with a close link to the industry. The mission has goals in education [1], technology demonstration and science. The mission brings Finland also to the widening circle of space faring nations as it is expected to be the first Finnish satellite launched. The original mission idea was developed by Aalto University students in 2010 and the satellite was designed and built as an university project together with wide academic and industrial consortium. The satellite platform was developed by university while the payloads were developed by various consortium partners. The main payload of the mission is a miniature hyperspectral camera AaSI. In this paper we give an overall description of the satellite and its hyperspectral Earth Observation (EO) payload with an emphasis on first in orbit results for EO mission.
2017 XXXIInd General Assembly and Scientific Symposium of the International Union of Radio Science (URSI GASS)